Quality of Life and Emotional Strain in Caregivers of Patients with Multiple Sclerosis - Petrikis, Petros (J Clin Neurol, 2019)
BACKGROUND AND PURPOSE: This study aimed was to measure the quality of life, fatigue, stress, and depression in a consecutive sample of caregivers of multiple sclerosis (MS) patients. METHODS: We included data from 131 consecutive caregivers of MS patients [age=51.2±12.8 years (mean±SD), males=53.4%, duration of caregiving=10.0±6.3 years]. We assessed the quality of life, fatigue, stress, and depression of the caregivers using the 36-item Short Form Health Survey, Krupp Fatigue Severity Scale, Kingston Caregiver Stress Scale, and Hamilton Scale for Depression, respectively. The disability status of the patients was assessed using the Kurtzke Expanded Disability Status Scale. We used linear regression models to identify possible correlations between all of the aforementioned scales, while multivariable logistic regression models were employed to assess the correlations of caregiver fatigue with caregiver characteristics and patient disability. RESULTS: The linear regression analyses revealed that caregiver fatigue was positively associated with stress and negatively correlated with both physical health status and mental health status. Caregiver stress was positively associated with depression and negatively correlated with both physical health status and mental health status. Depression was negatively correlated with both caregiver physical health status and mental health status. In multivariable logistic regression analysis, caregiver fatigue was found to be independently associated with education status [odds ratio (OR)=0.61, 95% CI=0.37 to 0.99], history of chronic disease (OR=5.52, 95% CI=1.48 to 20.55), other chronic diseases in the family (OR=7.48, 95% CI=1.49 to 37.47), and the disability status of the patient (OR=1.36, 95% CI=1.03 to 1.80). CONCLUSIONS: Fatigue, stress, and depression in caregivers of MS patients are negatively correlated with their physical health status and mental health status. Caregiver fatigue is independently associated with education status, history of chronic disease, other chronic disease in the family, and patient disability.